Assessment and comparative study of Entrance Skin Dose for digital panoramic x-Ray equipments - Bayan Saber Ibrahim; Hassan Ali Mahmood (Erbil Dental Journal)
Background and objective: A panoramic radiograph is a panoramic scanning dental x-ray of the upper and lower jaw. It shows a two-dimensional view of a half-circle. The aim of this study was to estimate of entrance surface dose (ESD) to the patient, in diagnostic panoramic radiology, to compare ESD (Entrance skin dose) for panoramic radiographies, analyze the relative advantage and disadvantage of their modalities.